Transformasi Sosial Dan Ekonomi Masyarakat Nelayan Etnis Melayu Ogan Di Perairan Lebak Lebung Desa Embacang Kabupaten Ogan Ilir Sumatera Selatan - Otoman Otoman; Maya Panorama; Kiki Mikail; Herison Herison (Tsaqofah, 2022)
The limitations of economic analysis carried out by economists seem partial and ahistorical, this condition opens up space for social scientists to explain further about the relationship between the economy and society that produces new scientific products, namely economic sociology. Economic sociology seeks to provide a more robust theory of economy and society than liberal economic or political economy. Economic sociology introduces various aspects related to tradition that can help in exploring the process of differentiation and integration. In discussing the economic development of the ethnic Malay fishing community of Ogan Lebak Lebung Public Waters, an economic sociology approach is used. The theory used is the Embeddeness-Granoveterian theory. The study was conducted on the Ogan Malay ethnic fishing community in Embacang Village, Ogan Ilir Regency, South Sumatra, where most of the people fish in the Ogan River. The results showed that at first the access of the Ogan Malay fishing community in Embacang village to the fishery resources in the area was managed by the clan government and transformed into being managed by the local government, this transformation resulted in a low level of income for the fishing community, even lower when compared to daily wage. This resulted in the economic action inherent in social relations in the Ogan Malay ethnic fishing community in Embacang Village, which during the reign of the clan lasted a lot and became entrenched. Meanwhile, the economic development of the Ogan Malay fishing community in Embacang Village has also transformed from an economic system with a traditional culture to a capitalist culture. Economic actions become individual actions that no longer consider various aspects of the social and cultural life of the community, except only for certain matters of a customary nature or character. only a very principled habit, which is a prestige in the local community. It can be said, that the transformation of the auction tradition (access) of PULL fisheries resources for the Ogan Malay ethnic fishing community in Embacang village led to the economic development of the community from a traditional culture to a capitalist culture. The economic action with a capitalist culture resulted in the erosion of social ties in the local community which during the reign of the clan was embedded in economic action.